If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 8 = 3x + -11 Reorder the terms: 8 + 4x = 3x + -11 Reorder the terms: 8 + 4x = -11 + 3x Solving 8 + 4x = -11 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 4x + -3x = -11 + 3x + -3x Combine like terms: 4x + -3x = 1x 8 + 1x = -11 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + 1x = -11 + 0 8 + 1x = -11 Add '-8' to each side of the equation. 8 + -8 + 1x = -11 + -8 Combine like terms: 8 + -8 = 0 0 + 1x = -11 + -8 1x = -11 + -8 Combine like terms: -11 + -8 = -19 1x = -19 Divide each side by '1'. x = -19 Simplifying x = -19
| [5-4x]=-3 | | -36-12/5= | | 1/6x13 | | -8k+2k=6-5k | | -7w=-14/9 | | -119=7(2x-5) | | 4x^2+21x-16=19-2x | | 11/12-(10)-5/6 | | 14x-5=6x+2 | | 6m=3m+6 | | -6/7w=12 | | 6h=5h+7 | | 4x+3-2x=25-4x+4 | | 2x+11x=1 | | -9y-9=-10y | | 3x-7=17-2x+6 | | x^2+xy+y^2=16 | | 2(6x+1)=3(2x-4) | | [x+a]=-4 | | 7.50+0.05x=0.08x | | 3e^3x+6=66 | | -4(3)-3y=9 | | 3(2x-1)-(x+2)=10 | | 12*-2t+3=96 | | 7.50+0.05x=0.08 | | 6-10z=-4z | | 30=b+s | | 3a+1=14 | | 175=(25)(7)+7 | | 5s-2a^2=0 | | -7n+3=-2n-7 | | -5x+40=8x-37 |